Management of electronical and electric equipment wastes and environmental and sanitary risks in Godomey and Abomey-Calavi boroughs in Bénin - AZONHE, THIERRY HERVÉ S. NICÉPHORE; ATEYIHO, Odette; BONI, GRATIEN; GOUISSI, Fadéby Modeste (My University, 2018)
The inadequate elimination of electronic wastes causes environmental pollution and dangers for human health. This study aims to analyze the health and environmental risks related to waste treatment processes for TV sets and computers at the dismantling sites in the Godomey and Abomey-Calavi boroughs. The chemical analysis of four soil samples taken from the dismantling sites was carried out. Heavy metals are measured. The average mercury (0.4064 μg/kg), lead (124.5 mg/kg) and cadmium (2.18 mg/kg) concentrations indicate soil pollution as a result of decommissioning and incineration of E-waste. Incineration sites are more exposed to lead in view of the high concentrations recorded at the sites, notably at Godomey-station (238 mg/kg) and Cococodji (188 mg/kg). Moreover, the lack of personal protective equipment (eyeglasses, gloves, work wear, mask) exposes workers’ site to frequent discomfort signs of serious pathological. The relative risk (RR) calculation to assess the relationship between the wearing of personal protective equipment PPE and the occurrence of discomfort among workers at dismantling sites for electrical and electronic equipment (WEEE) gave RR = 0.24 <1. The calculated fraction RPF risk = 0.76 or 76%. This led to the conclusion that the wearing of PPE makes it possible to avoid 76% of the discomforts in the ranks of site workers. In view of these findings, it is necessary that measures be taken to control and regulate metal recovery activities in WEEE and that modern procedures that can reduce health and environmental risks are implemented.
Keywords: Abomey-Calavi; Dismantling; WEEE; Environment; Health